Astrocytic Insulin-Like Growth Factor-1 Protects Neurons Against Excitotoxicity - Chen, Wei; He, Bin; Tong, Wusong; Zeng, Jinsong; Zheng, Ping (Frontiers in Cellular Neuroscience, 2019)
Background：Exogenous insulin like growth factor-1 (IGF-I) is known to be neuroprotective in animal models with brain insults, while it can also cause hyperexcitability in rodents. In this regard, the role of endogenous IGF-1 in brain responses to brain insults like excitotoxicity, a common pathology in brain injuries remains to be elucidated. Here, we investigated the potential role of cell-specific endogenous IGF-I in the kainic acid (KA) -induced degeneration of the neurons. Methods: KA was given to primary cultured cortical neurons and co-cultured astrocytes were added as a supportive system. We evaluated the cell proliferation rate, IGF-1 level in different groups and applied the PCR-Chip assay to explore the downstream of IGF-1. In addition, we applied the viral transfer of astrocytic IGF-1 to rodents treated with KA and assessed the associated molecular marker and behavioural outcomes in these rodents. Results: We found KA induced increased cell death and hyperphosphorylated tau in neurons; co-cultured astrocytes could prevent these pathologies, and this rescuing effect was abrogated with blockade of the astrocytic IGF-1 with AG1024 (IGF-1R inhibitor). PCR-Chip assay identified that astrocytic IGF-1 could decrease the p-GSK-3 at Tyr 216 in neurons treated with KA and this effect was abrogated with AG1024 as well. In addition, in-vivo study showed that gene transfer of astrocytic IGF-1 decreased p-tau and cognitive dysfunction in KA mice. Conclusion: Our results show astrocytic IGF-1 exhibit neuroprotective properties in neurodegenerative processes in the CNS.